Copolymerization of acrylic acid and 2- acrylamido-2-methylpropane sulfonic acid in supercritical carbon dioxide - Meleán Brito, Ramses Segundo (2024)
This study explores the copolymerization of acrylic acid and 2-acrylamido-2-methylpropane sulfonic acid (AMPS) in supercritical carbon dioxide (scCO2) as a sustainable alternative to traditional solvent-based methods. Using free-radical polymerization in scCO2, copolymers were synthesized without the need for additional drying. The influence of AMPS concentration in the feed on copolymer properties was investigated, achieving reactions with monomer conversions ranging from 61.3 to 92.9 mol%. Analytical characterization confirmed low AMPS incorporation across samples, with molar mass and hydrodynamic properties varying based on the AMPS content. Notably, two distinct polymer configurations were observed depending on whether the initial AMPS concentration was above or below 12 mol%, with polymers exhibiting molar masses between 13.2×10⁵ and 14.2×10⁵ g mol−1. Rheological analysis revealed that higher AMPS concentrations led to increased hydrodynamic radii, enhanced thickening capacity, and improved resistance to both monovalent (NaCl) and divalent (CaCl₂) salts in aqueous solutions.